Stability of the Severity of Intimate Partner Violence - Taylor, Ashley R. (Journal of interpersonal violence, 2021)
Prior research with a sample of male probationers indicates severity levels of one arresting intimate partner violence (IPV) offense are predictive of future frequency of such offenses and treatment completion. This study is an extended analysis looking at severity ratings across two IPV offenses to measure violence stability. The stability of IPV severity levels was analyzed in a sample of offenders in Lake County, Illinois. Offender subtypes of generally violent (GV) men and family only (FO) violent men were incorporated into stability analyses using generalized linear mixed modeling (GLMM) to determine whether certain types of offenders vary in violence levels over time. The purpose was to determine the predictive utility of using a single offense to determine the domestic violence trajectory for male probationers. Reoffense records of 80 men were collected from a larger sample of 352 males, ages 17 to 72 placed on probation in Lake County, Illinois, between 2006 and 2008. Severity of offenses was coded dichotomously based on a behaviorally derived measure. Results demonstrate 64% of reoffenders remained stable in IPV severity. Overall, severity levels decreased across time. This is the first study to use a probationary sample of men to analyze violence stability trends over time. This study confirms the utility of measuring a single offense to predict future violence trajectories for IPV offenders.